Region’s reputation and the price of regional products: a hedonic analysis of Portuguese quality cheese - Ribeiro, J. Cadima (2004)
Resources (tangible and intangible) can be mobilised to increase region’s reputation and confer a competitive advantage to certain products with origin in that region. The returns of a region’s resources depend upon the ability of local firms to appropriate the rents earned and whether the consumers value the characteristics of the region that are associated with the product, being disposed to pay a price premium. The estimation of a hedonic price function, which relates the price of portuguese regional cheeses to its various attributes, provided empirical support to the hypothesis that regional designation of origin maters to consumers. The study shows that some designations of origin, cheese characteristics (cured or not) and milk types have a significant impact on price. Particularly, while cheeses from regions of “Minho e Trás-os-Montes” and “Ribatejo e Estremadura” are expected to have price premiums, cheeses from regions of “Alentejo” and “Ilhas” are expected to have discounts, relative to “Beiras” (base category). Also, ewe’s cheese and no cured cheese have positive effect on price.